2019
DOI: 10.3390/ijms20051199
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of CAPE and Kaempferol in Colon Cancer Cell Lines—Possible Implications in New Therapeutic Strategies

Abstract: Background: Phytochemicals are natural compounds synthesized as secondary metabolites in plants and represent an important source of molecules with therapeutic applications. Attention is accorded to their potential in anti-cancer therapies as single agents or adjuvant treatment. Herby, we evaluated the in vitro effects of a panel of natural compounds with focus on caffeic acid phenethyl ester (CAPE) and Kaempferol for the treatment of human colon cancer. Methods: We exposed two human colon cancer cell lines, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 36 publications
0
39
0
2
Order By: Relevance
“…In order to evaluate the level of toxicity that was induced by the combined therapy and the morphological changes that were induced by the treatments, we used the triple staining protocol that was developed in our facility [23]. The mitochondrial networks were stained with Mitotracker-Red, the actin filaments were stained with Phalloidin-FITC, and the nucleus was stained with DAPI.…”
Section: Establishment Of Morphological Changes Induced After Single-mentioning
confidence: 99%
See 2 more Smart Citations
“…In order to evaluate the level of toxicity that was induced by the combined therapy and the morphological changes that were induced by the treatments, we used the triple staining protocol that was developed in our facility [23]. The mitochondrial networks were stained with Mitotracker-Red, the actin filaments were stained with Phalloidin-FITC, and the nucleus was stained with DAPI.…”
Section: Establishment Of Morphological Changes Induced After Single-mentioning
confidence: 99%
“…After 24 h of exposure to the half of the IC 50 and combined IC 50 treatments, the morphological changes induced by the treatments were assessed using the triple staining protocol previously published by our research team [23]. The cells were incubated on a chamberslide for 24 h with the treatment added.…”
Section: Morphological Analysis Of Confocal Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies evaluated the effect of the flavonol kaempferol, found in several plant derivatives (e.g., apples, onion, leeks, citrus, grapes, gingko biloba, St. John's wort, red wine), on several types of cancer [82][83][84][85][86]. The antitumor effects of kaempferol were evaluated in hepatocellular carcinoma (HCC) cells.…”
Section: In Vitro-and In Vivo-mediated Autophagy By Polyphenolsmentioning
confidence: 99%
“…In addition, these anticancer effects may be partly due to the antioxidant properties of the flavonoids, and recent studies suggest that interactions with essential signal transduction pathways may be more important (Alaklabi et al 2018;Ojelabi et al 2018). As well, flavonoids may also interact with chemotherapeutic drugs used in cancer treatment through the induction or inhibition of their metabolism (Budisan et al 2019).…”
Section: Epidemiological Evidences On the Role Of Dietary Flavonoids mentioning
confidence: 99%